Comparative study of the effects of intranasal midazolam with intranasal dexmedetomidine as premedication in paediatric anaesthesia - Mohanraj, Parthasarathy; Narendrababu, M. C. (International Journal of Research in Medical Sciences, 2024)
Background: Premedication in children is more acceptable with the intranasal route. In this study, we evaluated the efficacy of intranasal dexmedetomidine as premedication in paediatric surgeries as compared to intranasal midazolam. Methods: This study was conducted in 60 patients of 6 to 12 years posted for tonsillectomy surgeries. Patients were randomly allocated into Group 1 and 2. Patient in group 1 (30) received 0.2mg/kg of intranasal midazolam as nasal drop using 1ml insulin syringe and similarly group 2 (30) received 1µg/kg of intranasal dexmedetomidine as nasal drops using 1ml insulin syringe. Sedation score, Anxiolysis score, pre oxygenation mask holding response score, post-operative agitation scores were evaluated. Results: In our study, we observed that 76.7% of children in dexmedetomidine group attained better sedation compared to 46.7% in midazolam group. Anxiolytic effect in Group 1 (83.3%) was slightly better than in Group 2 (80%). 90% of the patients in dexmedetomidine group allowed easy pre oxygenation compared to 80% in midazolam group. Venipuncture response was better with dexmedetomidine group (86.7%) compared to midazolam group (73.3%). Postoperative agitation response in both the groups was same. The fall in HR, SBP was more with dexmedetomidine and there was no significant change in DBP in both the groups. Conclusions: From our study, we concluded that premedication with intranasal dexmedetomidine is more effective than intra nasal midazolam in providing sedation. Both the drugs are effective in providing anxiolysis and better inducing condition. Therefore, intranasal dexmedetomidine is more efficacious than intranasal midazolam as premedication in children.